Translating Runyankole- Rukiga Folktales Into English. - Tukaheebwa, Miria (Kabale University, 2024)
The study explored the folktales in Runyankole-Rukiga and translated them into English. The research questions addressed were: to find out different folktales in Runyankole-Rukiga and translate them into English, and to establish the different significances of such folktales. From the 2 questionnaires distributed to lecturers. The research used a qualitative method which was employed to assess and acquire clear explanations of the different patterns of knowledge, and practices perceived in translating folktales from Runyankole-Rukiga to English. Research findings showed that three folktales adopted from Mr. Karwemera's folktales were successfully translated from RR into English. The study also concludes that through this translation process whereby the researcher got a chance to meet with language experts and educationists, it was observed that learners who study in their mother language are able 'O understand concepts better than those who learn in a foreign language. Folktales bring out the richness of a language and the culture, once one uses a story in l1is communication; it enriches his message and keeps the listeners' interest. It is understood that the translation of folktales has helped in developing different language's orthography and lexical which has led to language and culture preservation whereby people get to know how to tell different folktales in different areas. Folktale translation have helped to avail information to communities in that it gives the inner meanings of different folktales and then users get to know which lesson they get from them. The researcher also found out that there are few folktales in Runyankole Rukiga and therefore finding them for translation is still a problem. The study recommends that folktale books in Runyankole¬Rukiga should be written, published, and distributed in schools to have an increased number of references for students in schools and other educational institutions Lessons of translation should be introduced in lower classes such that learners grow up while knowing their cultural folktales and this will improve folktale usage. The translation should have its courses, examinations, career structures, and professional organizations in Uganda. Therefore. it is prudent that we intellectualize, industrialize, and commercialize our Ugandan languages¬